SOME PERSPECTIVES FOR INTRODUCING ELEMENTS OF CREATIVE DRAMA TECHNIQUES INTO UNIVERSITY FOREIGN LANGUAGE COURSES - Крекотень, Олена (SWorldJournal, 2024)
The paper is aimed at the determining of effective methods of creative dramatization in foreign language teaching at universities as well as analyzing of scientific literature concerning the problem. The modern drama approaches to updating the foreign lan